Tinjauan Praktik Pendidikan Anak Usia Dini (PAUD) dalam Kerangka Pendidikan Islam - Mohamad Samsudin; Nur Afiyah (Al Ashriyyah, 2022)
Review of Practice of Early Childhood Education in the Framework of Islamic Education. This paper aims to explain whether the concept of Islamic education inspires the practice of early childhood education or not. Because conceptually, Islam has explained how to educate children early on with a good and true. But in reality, early childhood education is still far from the concept of Islamic education. This is due to many factors that develop in the world of education itself, including parents' ignorance of the importance of children's education, in addition to the wrong paradigm in seeing children as students. Therefore, efforts to reorient the education of early childhood on the basis of Islam needs to be done.